Impact of Orthopedic Hand Surgery Fellowship Training on Hand Surgery Cases Performed by Plastic Surgeons in the United States - Silvestre, Jason; Levin, L Scott; Wilson, Robert H.; Chang, Benjamin (Journal of Hand and Microsurgery, 2023)
Objective Multiple pathways exist for hand surgery training in the United States. Plastic surgeons often select Orthopedic Hand Surgery Fellowships to complement their skills and bridge perceived deficiencies in bone and joint cases. This study aims to quantify the impact of this approach on operative hand experience.Materials and methods Case logs were analyzed for plastic surgery residents and orthopaedic hand surgery fellows (2016–2017 to 2019–2020). Reported hand surgery cases were compared between residency and fellowship using Student's t-tests. In total, 606 plastic surgery residents and 393 orthopaedic hand surgery fellows were included in this study. One year of Orthopedic Hand Surgery Fellowship training afforded more than twice the volume of hand surgery cases than Plastic Surgery Residency training (886.1 ± 234.7 vs. 428.1 ± 147.2, p < 0.001).Results Case categories with the greatest positive fold difference in case volume encountered during Orthopedic Surgery Hand Fellowship were tumor (138.2 ± 63.2 vs. 22.1 ± 11.8, p < 0.001), joint reconstruction (108.7 ± 21.6 vs. 18.8 ± 11.5, p < 0.001), nerve decompression (158.4 ± 63.1 vs. 53.0 ± 32.6, p < 0.001), Dupuytren's (18.4 ± 10.5 vs. 7.6 ± 6.4, p < 0.001), and fracture management (132.8 ± 21.7 vs. 59.6 ± 24.1, p < 0.001).Conclusion Orthopedic Hand Surgery Fellowship training doubles the operative hand case volume encountered during Plastic Surgery Residency. Significant increases are especially encountered for select case categories including bone and joint cases.
Keywords: fellowship; hand; academic; surgery; residency; orthopaedics